The association of depression and angina pectoris across 47 countries: Findings from the 2002 World Health Survey - Loerbroks, Adrian; Bosch, Jos Antonio; Mommersteeg, Paula Maria Christina; Herr, Raphael M.; Angerer, Peter; Li, Jian (European Journal of Epidemiology, 2014)
Comorbid depression predicts poor health outcomes in patients with angina pectoris (AP). However, epidemiological data on the depression-AP comorbidity is limited and largely restricted to studies from Western countries, making generalizability to other regions uncertain. We aimed to provide additional epidemiological data for non-Western as well as Western countries. The present study used population-based data gathered in 47 countries from four continents (Africa, Asia, South America, and Europe) included in the cross-sectional 2002 WHO World Health Survey. Self-reported indicators of depression included: (a) its diagnosis, (b) its treatment, and (c) seven symptom items to determine presence of a major depressive episode. Similarly, information on AP comprised (a) a self-reported diagnosis, (b) self-reported AP treatment, (c) and a definition according to the WHO Rose questionnaire. In primary analyses, we operationalized depression or AP as positive if any of the respective indicators was present. Associations were estimated by multivariate logistic regression. In the entire sample (n = 213,264), the odds of AP were more than doubled among those with depression [odds ratio (OR) = 2.60, 95 % confidence interval = 2.36, 2.87] versus those without depression. These positive associations were replicated across all continents and were observed in both men and women. Likewise, meaningful associations (ORs ≥ 1.5) were observed in virtually all individual countries (46/47). Application of different operationalizations of depression and AP confirmed the above findings, both in the entire sample and in continent-specific analyses. Our study extends the current evidence accrued in Western populations to non-Western populations. The co-occurrence of AP and depression appears to represent a universal phenomenon. © 2014 Springer Science+Business Media.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Angina pectoris; Depression; Epidemiology; World Health Organization